Paradigma Pendekatan Ilmu Sosial-Humaniora dalam Kewarganegaraan dan Keberagamaan - Mukhlishi Mukhlishi (JURNAL KEISLAMAN TERATEKS, 2016)
One of the hotbeds flowering of law is the problem of social life and contemporary issues. To open the horizons of academics and practitioners need to be confronted with the problem of social life and contemporary issues. They dituntutberfikir hard to assess, understand, look for the solution of social problems in your life. What is the meaning of a person’s faith if it is not susceptible to a question of life and the nation’s neighbors. Yet according to the true religion there is a very strong linkage which can not be disconnected between spiritual intelligence with social intelligence. To understand the teachings of the first through the text, because the text are the symbols and values, and then needed a contextual understanding, and komperhensip because the law there are born and live in a vacuum. In addition, people who practice have never been aware of a law without knowing their mashlahah behind. Contextual understanding to be assessed holistically, through the paradigm of social-humanities with an effort to combine form Multiperspective paradigms and theories of contemporary scientific and attention to the elements of the legal, philosophical, the psychological, sociological, cultural and anthropological. Such an approach is necessary and should be appreciated by academics.